Borysenko D.V. Modern models of state cultural policy implementation in develo-ped world - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The advanced international experience of state cultural policy implementation has been researched. The basic models of implementing state policy in the  eld have been identied.